Colombia : Review Under the Flexible Credit Line Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Colombia. (IMF Staff Country Reports; Country Report ;, 2021)
COVID-19 has taken a severe toll on Colombia's society and economy-including over 60,000 deaths and over 5 million jobs temporarily lost in Colombia's largest recession on record. A gradual but uneven recovery led by private domestic demand and manufacturing is underway, but services continue to be weak. While the economy had remained resilient before the pandemic owing to very strong policy frameworks, economic activity is not expected to return to pre-pandemic levels until the end of 2022.